Isolation and characterization of culturable actinobacteria associated with Polytrichum strictum (Galindez Island, the maritime Antarctic) - Gromyko, O.; Tistechok, S.; Roman, I.; Aravitska, O.; Luzhetskyy, A.; Parnikoza, I.; Fedorenko, V. (Ukrainian Antarctic Journal, 2021)
The main objective of the study is the evaluation of the diversity of actinobacteria associated with Polytrichum strictum — dominant species of widespread Antarctic Тall moss turf subformation and their characteristics as the producers of biologically active compounds. The actinobacterial isolates were isolated by direct inoculation, phenol pretreatment, and heated treatment. The cultural properties of the isolates were evaluated using diagnostic media. The antimicrobial activity of the isolates was determined by the point inoculations method. The phylogenetic analysis was based on sequence analysis of the 16S rRNA gene. The biosynthetic genes screening was performed using polymerase chain reaction. A total of 23 actinobacterial isolates associated with P. strictum were isolated, the four identified genera being Streptomyces (7 isolates), Micromonospora (14 isolates), Kribbella (1 isolate), and Micrococcus (1 isolate). Eight psychrotrophic strains of all identified genera were identified. The optimal pH values for all isolates were in the range 6–10. Four isolates grew on the medium with 7.5% NaCl. A significant number of the isolates showed a wide range of enzymatic activities. Antagonists of a wide range of pathogenic microorganisms were found, including against multidrug-resistant strain of Candida albicans and Methicillin-resistant Staphylococcus aureus. Some strains were active against phytopathogenic bacteria, namely three strains against Erwinia amylovora, one strain against Agrobacterium tumefaciens, and one strain against Pectobacterium carotovorum. More than half of the isolates showed antifungal activity against Fusarium oxysporum and Aspergillus niger. The biosynthetic genes involved in synthesizing a wide range of bioactive compounds were found in more than 80% of isolates. Antarctic actinobacteria isolated in this study demonstrate potential as the producers of a wide range of biologically active compounds. Further studies of these actinobacteria may lead to the identification of previously unknown biologically active compounds.